MAPCART - Goudarzi, Saman; Glover, Bronwen; Penfold, Kelly (Bulletin - Association of Canadian Map Libraries and Archives (ACMLA), 2025)
This manual addresses the challenges associated with the physical handling of flat sheet maps, advocating for the use of concave supports during their transportation. It provides an alternative to commercially procured map carts by offering step-by-step instructions and illustrations for constructing a map cart in-house.